Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Pada Toko Hana Fashion Jakarta Barat (Studi Penjualan Online) - Meysa Wardaniagari Putri; Nurhadi Nurhadi (International Forum of Researchers and Lecturers, 2025)
Product Quality is the result of a product that has been made with human labor so that it becomes a product that can be traded among consumers. Price is an amount of money that will be exchanged for an item needed by consumers, thus making many consumers to make purchasing decisions on products. The purpose of the marketing department is to promote goods with the beauty of the product and make consumers interested so that they make the decision to buy the item. The purpose of this study was to determine and analyze whether product quality and price affect purchasing decisions at the hana fashion shop in West Jakarta. This type of research is using a quantitative approach in a measurable way. The population in this study were all consumers who bought hana fashion store products. The sampling technique in this study used purposive sampling, namely by determining the sample based on the objectives and considerations of the researcher and consumers who buy hana fashion products. The information collection strategy used by researchers is based on a questionnaire that has been distributed to 80 people. The results of this statement indicate that product quality has a significant influence on purchasing decisions. Price has a significant influence on purchasing decisions.